Saccharomyces boulardii modulates and improves the immune response to Bovine Herpesvirus type 5 Vaccine - Roos,T.B. (2018)
ABSTRACT There have been significant efforts towards the development of more efficient vaccines for animal health. A strategy that may be used to improve vaccine efficacy is the use of probiotics to enhance the immune response of the host, leading to increased immunogenicity of antigen preparations. Bovine herpesvirus 5 (BoHV-5) is an example of an important animal pathogen for which vaccines have provided only limited protection. In this study, we examined the use of the probiotic Saccharomyces boulardii (Sb) as a potential adjuvant to improve vaccine efficiency. We found that the supplemented animals exhibited an enhanced systemic IgG antibody response toward a Th1 response in favor of IgG2a and increased mRNA expression levels of the cytokines IFN-y, IL-12, IL-17 and IL-10 in the spleen. These results suggest that Sb supplementation may provide a promising means for improving the efficiency of vaccines, particularly those that rely on a cell-mediated immune response.